2018
DOI: 10.1016/j.jbi.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Archetype modeling methodology

Abstract: Clinical Information Models (CIMs) expressed as archetypes play an essential role in the design and development of current Electronic Health Record (EHR) information structures. Although there exist many experiences about using archetypes in the literature, a comprehensive and formal methodology for archetype modeling does not exist. Having a modeling methodology is essential to develop quality archetypes, in order to guide the development of EHR systems and to allow the semantic interoperability of health dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…This study was performed using the approach suggested by Bacelar-Silva et al [30] Braun et al [31] and Moner et al [32], comprising the following sequential steps ( Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed using the approach suggested by Bacelar-Silva et al [30] Braun et al [31] and Moner et al [32], comprising the following sequential steps ( Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the selected concepts were modelled as openEHR archetypes. Archetype modelling has been widely applied in previous studies [30,32,34]. The concepts were discussed by the authors and relevant items were identified from books, journal articles, and guidelines.…”
Section: Archetype Modelling In Openehrmentioning
confidence: 99%
“…To find relevant archetypes from the open repository, we first had to understand which kinds of terms end users tended to enter. As archetype modeling methodology [23] shows, domain experts identify core clinical concepts and related data elements involved in a particular scenario and organize them into mind maps or design tables. These archetype design specifications are the main source of search keywords.…”
Section: Methodsmentioning
confidence: 99%
“…Archetypes are general purpose, reusable, and composable; therefore, searching for reusable archetypes from archetype repositories is essential throughout the development process [22,23]. Documents with complete archetype design specifications are the input; lists of existing reusable archetypes, either complete or needing modifications, and new archetypes to be developed from scratch are the output [23]. The crucial problem is how to find the relevant ones from open repositories to help identify reusable archetypes.…”
Section: Introductionmentioning
confidence: 99%
“…Moner et al [16] define an Archetype Modeling Methodology (AMM). The main phases of the methodology are briefly described below.…”
Section: Archetype Modeling Methodologymentioning
confidence: 99%